PARP inhibition and synthetic lethality in ovarian cancer. Issue 5 (September 2014) - Eskander, Ramez N; Tewari, Krishnansu S
<x xml:space="preserve">Abstract</x> Ovarian cancer is the leading cause of gynecologic cancer death in women. Our understanding of the treatment of ovarian cancer has evolved over the last decade, with the use neo-adjuvant chemotherapy, combined intravenous-intraperitoneal (IV-IP) chemotherapy, as well as dose dense paclitaxel. Despite significant improvements in overall survival, the majority of patients succumb to recurrent chemotherapy resistant disease. Given the above, an emphasis has been placed on exploring alternate therapeutics. Recent research efforts have improved our understanding of the molecular biology of ovarian cancer and novel targeted treatment strategies have emerged. With the discovery of BRCA1 and BRCA2 gene mutations, and a more comprehensive assessment of heredity ovarian cancer syndrome, targeted interventions exploiting this biologic susceptibility have emerged. To date, the most studied of these have been PARP inhibitors. The purpose of this review will be to discuss PARP inhibition in advanced stage ovarian cancer, highlighting recent scientific advancements.